2015
DOI: 10.1039/c5ra07403g
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous nano-MFI zeolite-pillared montmorillonite clay synthesized by recrystallization for hydrocracking of residual oil

Abstract: A MFI zeolite nanosheet-pillared montmorillonite clay (MPC) composite material has been synthesized under hydrothermal conditions by a recrystallization method. The hierarchical porous material possesses uniform micropores in the crystalline zeolite pillars and uniform mesopores between the 10 65 A MFI zeolite nanosheet-pillared montmorillonite clay (MPC) with uniform hierarchical structure was synthesized by a recrystallization method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Recently, considerable attention has been paid to layered zeolites with a thickness varying from one to several unit cells. These systems possess short diffusion lengths, potentially overcoming diffusion and mass transfer limits. Various types of zeolites have been synthesized in the nanosheet form with different possible interlayer linkers , with an aim at targeting various catalytic systems such as isomerization and hydrocracking, selective formation of molecules, , and epoxidation reactions. Although zeolite nanosheets have been also considered for adsorption and membrane separation systems, zeolite nanosheets specifically as RO membranes for water desalination have been greatly overlooked in the literature. The small thickness of layered zeolites (i.e., short diffusion distance) along with their excellent chemical and physical resistance make zeolite nanosheets a promising type of RO membrane materials in water desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable attention has been paid to layered zeolites with a thickness varying from one to several unit cells. These systems possess short diffusion lengths, potentially overcoming diffusion and mass transfer limits. Various types of zeolites have been synthesized in the nanosheet form with different possible interlayer linkers , with an aim at targeting various catalytic systems such as isomerization and hydrocracking, selective formation of molecules, , and epoxidation reactions. Although zeolite nanosheets have been also considered for adsorption and membrane separation systems, zeolite nanosheets specifically as RO membranes for water desalination have been greatly overlooked in the literature. The small thickness of layered zeolites (i.e., short diffusion distance) along with their excellent chemical and physical resistance make zeolite nanosheets a promising type of RO membrane materials in water desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many efforts are made to develop new types of catalysts based on hierarchical zeolites in the HDC reaction. ,, Introducing mesopores into the zeolites or reducing the zeolite crystalline size can efficiently overcome the diffusion limitations and significantly accelerate the mass transfer to and away from the catalytic centers, thus reducing the possibility of secondary reactions which cause coke formation and catalyst deactivation . Therefore, catalyst supports with open hierarchical pore structures contribute to high catalytic activity.…”
Section: Applicationsmentioning
confidence: 99%
“…Utilizing the lower boiling point of the (shorter) cracked products to separate them out of a reaction mixture, process conditions can be found to minimize secondary reactions that lead to the formation of gasoline and gas, but this is effective only at low wax conversions over Pt on amorphous silica–alumina (ASA) . Recent advances in the control over noble-metal location as well as in the preparation of mesoporous zeolites , have demonstrated that catalyst improvement can lower the degree of secondary cracking for several model and real feeds. Pure primary cracking, the breaking of only one carbon–carbon bond in the reactant, has been observed since the earliest description of n -hexadecane ( n -C 16 ) hydrocracking over Pt/ASA and subsequently in the ideal hydrocracking of n -C 16 over the more active large-pore Pt/Ca-Y zeolite . In ideal hydrocracking a strong (de)­hydrogenation activity maintains a steady-state concentration of n -alkenes high enough to displace the alkylcarbenium ions from the acid sites through competitive adsorption.…”
Section: Introductionmentioning
confidence: 99%